2015
DOI: 10.1159/000370242
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Characteristics of Patients with Liver Cirrhotic Ascites

Abstract: Chronic hepatitis B is a common and frequently encountered disease in our country, the final outcome of which develops into liver cirrhosis and primary liver cancer.It was the aim of this study to provide a theoretical basis for the early diagnosis and treatment of liver cirrhosis. Ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS) is used to analyze endogenous bioactive substance change in healthy controls and patients with liver cirrhotic ascites. A metabolic fingerprint spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…The decrease in proline level in patients' sera can be explained by the high consumption of proline in more collagen biosynthesis in liver cirrhosis. Results in HCC by Chan W (41) and evaluations of patients with liver cirrhotic ascites by Yang T showed decreased in proline (42). Our study showed that the levels of VLDL were reduced in the decompensated LC group compared to healthy controls.…”
Section: Cytosolic Pathwaysupporting
confidence: 49%
“…The decrease in proline level in patients' sera can be explained by the high consumption of proline in more collagen biosynthesis in liver cirrhosis. Results in HCC by Chan W (41) and evaluations of patients with liver cirrhotic ascites by Yang T showed decreased in proline (42). Our study showed that the levels of VLDL were reduced in the decompensated LC group compared to healthy controls.…”
Section: Cytosolic Pathwaysupporting
confidence: 49%
“…Other studies showed that greater concentration of lysoPC in hepatic tissue are observed in non-alcohol steatohepatitis patients compared to healthy controls (Puri et al, 2007; Han et al, 2008). Finally, Yang et al (2014) showed that lysoPCs were identified as a potential biomarker for early diagnosis of liver fibrosis and cirrhosis. In the current study, the levels of lysoPCs (16:0, 18:2, and 22:6) were detected to be significantly higher in the LC group compared to the control group at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…In this view, the present work aimed to apply GC-MS based urine metabolomics of LC and HCC patients using untargeted analysis for novel biomarkers identification and to explore metabolites changes in these patients compared with healthy subjects. Yuan, Wang, Zhao, & Chen, 2013;Yang, Zheng, Xing, Zhuo, & Liu, 2014).…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%
“…PCA model (a) and ROC curve (b) for differentiation between LC and control groups Yuan,Wang, Zhao, & Chen, 2013;Yang, Zheng, Xing, Zhuo, & Liu, 2014).…”
mentioning
confidence: 99%